1983
DOI: 10.1159/000182960
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Administration Enhances Renal Protein Metabolism after Acute Tubular Necrosis

Abstract: The capacity of exogenous amino acids to alter renal protein metabolism was studied during renal regeneration after mercuric chloride-induced acute tubular necrosis in the rat. In regenerating cortical tissue, the free leucine concentration was 17% lower than normal, and was decreased further after glucose infusion. The concentration was raised above normal by amino acid infusion thereby ameliorating the deficit of this amino acid. Synthesis and degradation of rapidly-turning over proteins in renal cortical ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Starvation accelerates protein breakdown and impairs protein synthesis in the kidney while refeeding exerts the opposite effect [47]. In the experimental animal, the provision of amino acids or total parenteral nutrition accelerates tissue repair and recovery of renal function [48]. In patients this has been much more difficult to prove.…”
Section: Impact Of Nutritional Interventions On Renal Function or Recmentioning
confidence: 99%
“…Starvation accelerates protein breakdown and impairs protein synthesis in the kidney while refeeding exerts the opposite effect [47]. In the experimental animal, the provision of amino acids or total parenteral nutrition accelerates tissue repair and recovery of renal function [48]. In patients this has been much more difficult to prove.…”
Section: Impact Of Nutritional Interventions On Renal Function or Recmentioning
confidence: 99%
“…The plasma levels of ENAA are reduced in untreated patients [43], dialysis treatment will result in losses of both types of amino acids [45], and, more fundamentally, the availabil ity of sufficient amounts of all amino acids may be criti cal for protein synthesis [46]. In support of this notion is the work of Toback et al [28,47] who found that infusion of an ENAA solution was associated with an increase in renal cell protein and phospholipid synthesis in the mer curic chloride treated rat.…”
Section: Optimum Nutritional Intake In Arfmentioning
confidence: 98%
“…Further. Toback et al [28] and Toback [29] studied the rate of protein and phospholipid synthesis in renal tissue from rats with mercuric chloride induced ARF and found that the regeneration of renal tissue, as indicated by increased l4C-choline incorporation into membrane phospholipids, is markedly increased as compared to normal renal tis sue.…”
Section: Catabolism In Arfmentioning
confidence: 99%
See 1 more Smart Citation
“…Simple exposure (not dialysis) to cellulosic membranes may result in net protein catabolism [51] which continues for up to 9 h after exposure to the bioincompatible membrane. In addition, the dismal nitrogen balances achieved with standard approaches (lowprotein diet and conventional haemodialysis) to the nutritional management of these patients [52] are unacceptable in view of current thinking in the area of nutrition for the critically ill [53][54][55][56][57][58][59] and acute renal failure [60,61]. With the use of continuous therapies and the increased administration of protein nitrogen, patients with critical illness can move progressively toward the nutritionally important goal of a near neutral nitrogen balance.…”
Section: Pathophysiological Derangements and Renal Replacementmentioning
confidence: 99%